Respuesta :

Kheazy

Answer:

11

Step-by-step explanation:

[tex]n + 1 = 4(n - 8) \\ n + 1 = 4n - 32 \\ 4n - n = 1 + 32 \\ 3n = 33 \\ n = 11[/tex]

Answer: n = 11

Step-by-step explanation: n + 1 = 4(n-8)

                                             n + 1 = (4)(n) + (4)(-8)

                                             n + 1 = 4n + -32

                                             n + 1 = 4n - 32

                                             n + 1 - 4n = 4n - 32 - 4n

                                            -3n + 1 = -32

                                            -3n + 1 - 1 = -32 - 1

                                            -3n = -33

                                            -3n/-3 = -33/-3

                                             n = 11